Ferroptosis in cardiovascular disease: regulatory mechanisms and therapeutic implications - Zhao, Yiheng; Linkermann, Andreas Günter; Takahashi, Masafumi; Li, Qingguo; Zhou, Xiang (European heart journal, 2025)
Ferroptosis, an iron-dependent form of regulated cell death, has been identified as a key factor in the pathogenesis and progression of various cardiovascular diseases (CVDs). The molecular basis of ferroptosis involves lipid peroxidation, iron dysregulation, and antioxidant pathways. Accumulating evidence suggests that ferroptosis is associated with various CVDs, including atherosclerosis, myocardial ischaemia-reperfusion injury, cardiac hypertrophy, and diverse cardiomyopathies. In addition to ferroptosis inhibitors, several novel ferroptosis-targeting therapies have emerged, including new uses for existing drugs, plant-derived compounds, and targeted drug delivery. This review synthesizes current knowledge, identifies research gaps to summarize the complex regulatory mechanisms of ferroptosis, and provides an overview of its functions in CVDs. The innovative therapeutic strategies targeting ferroptosis may lead to a paradigm change in the treatment of CVDs.